CUSTOMER INTELLIGENCE PRACTICES IN DYNAMIC FIRMS: CAPTURING VALUE FROM THE CRM ECOSYSTEM - Rahman, Nayeem (My University, 2019)
Customer relationship management (CRM) platforms have recently overtaken database management systems to be the largest of all software markets in terms of yearly revenue. However, despite its increasing prominence as a source for customer intelligence, the nature of its effect on value creation in decision-making terms is not that well researched. This thesis addresses this gap particularly from a managerial point of view. The study opens with an extensive literature review, where two pillars of dynamic capabilities – sensemaking and absorbtive capacities (ACAP) – forms the theoretical backbone. Through the discussions, the thesis establishes a linkage between BI literature from a CRM angle with the more classical resource-based view of the firm. As a qualitative multiple case study ten case companies are investigated for this research. The cases are divided into two clusters for structural clarity and CRM influences on both are documented separately. Afterwards the results are aggregated for a holistic picture about CRM driven decision-making. The results identify the ways in which CRM tools are helping managers to maintain an organizational homogeneity by facilitating employee collaboration, how it guides through the customer negotiation phase, as well as how it allows firms to react fast and comprehensively with customer woes. The thesis also identified challenges associated with CRM integrational issues, motivational factors inhibiting CRM adoption, and suggests ways CRM can be better utilized for businesses of different scopes.
Keywords: customer relationship management (CRM); business intelligence (BI); customer intelligence; dynamic capabilities; sensemaking; absorbtive capacities (ACAP); fi=Master’s Programme in Strategic Business Development|